Nurse compliance with a protocol for safe injectable medication administration: comparison of two multicentre observational studies - Martine de Bruijne; Peter Spreeuwenberg; Cordula Wagner; Bernadette Schutijser; Joanna Ewa Klopotowska; Irene Jongerden (BMJ Open)
Objectives Medication administration errors with injectable medication have a high risk of causing patient harm. To reduce this risk, all Dutch hospitals implemented a protocol for safe injectable medication administration. Nurse compliance with this protocol was evaluated as low as 19% in 2012. The aim of this second evaluation study was to determine whether nurse compliance had changed over a 4-year period, what factors were associated over time with protocol compliance and which strategies have been implemented by hospitals to increase protocol compliance.Methods In this prospective observational study, conducted between November 2015 and September 2016, nurses from 16 Dutch hospitals were directly observed during intravenous medication administration. Protocol compliance was complete if nine protocol proceedings were conducted correctly. Protocol compliance was compared with results from the first evaluation. Multilevel logistic regression analyses were used to assess the associations over time between explanatory variables and complete protocol compliance. Implemented strategies were classified according to the five components of the Systems Engineering Initiative for Patient Safety (SEIPS) model.Results A total of 372 intravenous medication administrations were observed. In comparison with 2012, more proceedings per administration were conducted (mean 7.6, 95% CI 7.5 to 7.7 vs mean 7.3, 95% CI 7.3 to 7.4). No significant change was seen in complete protocol compliance (22% in 2016); compliance with the proceedings ‘hand hygiene’ and ‘check by a second nurse’ remained low. In contrast to 2012, the majority of the variance was caused by differences between wards rather than between hospitals. Most implemented improvement strategies targeted the organisation component of the SEIPS model.Conclusions Compliance with ‘hand hygiene’ and ‘check by a second nurse’ needs to be further improved in order to increase complete protocol compliance. To do so, interventions focused on nurses and individually tailored to each ward are needed.